KEMAMPUAN KONEKSI MATEMATIS SISWA SD MELALUI CIRCUIT LEARNING - Jayanti Putri Purwaningrum (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2016)
Abstrak. Penelitian ini bertujuan untuk mengkaji: (1) perbedaan rata-rata antara hasil tes kemampuan koneksi matematis siswa dengan Kriteria Kentutasan Maksimum (KKM) pada siswa yang belajar melalui circuit learning; (2) kemampuan koneksi matematis siswa yang belajar melalui circuit learning mencapai ketuntasan klasikal 75%; (3) circuit learning dapat meningkatkan kemampuan koneksi matematis siswa; dan (4) respon siswa tehadap pembelajaran matematika melalui circuit learning. Metode penelitian yang digunakan adalah pre experimental design, dengan desain one group pretest-posttest. Subjek dalam penelitian ini adalah siswa-siswi kelas IV pada salah satu SD di Kabpuaten Kudus dengan banyaknya siswa adalah 20 siswa. Instrumen penelitian yang digunakan yaitu tes kemampuan koneksi matematis, perangkat pembelajaran, skala sikap siswa dan lembar observasi. Hasil penelitian menyatakan: (1) terdapat perbedaan rata-rata antara hasil tes kemampuan koneksi matematis siswa dengan Kriteria Kentutasan Maksimum (KKM) pada siswa yang belajar melalui circuit learning; (2) kemampuan koneksi matematis siswa yang belajar melalui circuit learning mencapai ketuntasan klasikal 75%; (3) circuit learning dapat meningkatkan kemampuan koneksi matematis siswa; dan (4) siswa merespon positif tehadap pembelajaran matematika melalui circuit learning. Kata Kunci: Kemampuan Koneksi Matematis, Circuit Learning Abstract. This study aims to assess: (1) the different average between the results of students' mathematic connection ability test with the Kriteria Kentutasan Maksimum (KKM) on students who learn through the learning circuit; (2) the ability of students mathematic connections who learn through circuit learning reaches classical completeness 75%; (3) circuit learning can improve students' mathematic connections ability; and (4) the students’ respons of learning mathematics through circuit learning. The method of the research used is pre experimental design, with one group pretest-posttest design. Subjects in this study are students of grade IV at one of the primary school in the Kudus Regency with the number of students is 20 students. The research instrument used is the mathematic connection ability test, learning tools, students' attitudes scale and observation sheet. The study states: (1) there is a difference between the average the results of students' mathematic connection ability test with the Kriteria Kentutasan Maksimum (KKM) on students who learn through the learning circuit; (2) the ability of students mathematic connections who learn through circuit learning reaches classical completeness 75%; (3) circuit learning can improve students' mathematic connections ability; and (4) students respond positively on mathematic learning through circuit learning. Keywords: Mathematic Connection Ability, Circuit Learning